Oxidation of Cyclohexane to Cylohexanol and Cyclohexanone Over H4[a-SiW12O40]/TiO2 Catalyst - Aldes Lesbani; Fatmawati Fatmawati; Risfidian Mohadi; Najma Annuria Fithri; Dedi Rohendi (Universitas Gadjah Mada, 2016)
Oxidation of cyclohexane to cyclohexanol and cyclohexanone was carried out using H4[a-SiW12O40]/TiO2 as catalyst. In the first experiment, catalyst H4[a-SiW12O40]/TiO2 was synthesized and characterized using FTIR spectroscopy and X-Ray analysis. In the second experiment, catalyst H4[a-SiW12O40]/TiO2 was applied for conversion of cyclohexane. The conversion of cyclohexane was monitored using GC and GCMS. The results showed that H4[a-SiW12O40]/TiO2 was successfully synthesized using 1 g of H4[a-SiW12O40] and 0.5 g of TiO2. The FTIR spectrum showed vibration of H4[a-SiW12O40] appeared at 771-979 cm-1 and TiO2 at 520-680 cm-1. The XRD powder pattern analysis indicated that crystallinity of catalyst still remained after impregnation to form H4[a-SiW12O40]/TiO2. The H4[a-SiW12O40]/TiO2 catalyst was used for oxidation of cyclohexane in heterogeneous system under mild condition at 2 h, 70 °C, 0.038 g catalyst, and 3 mL hydrogen peroxide to give cyclohexanone as major product.